Rediscovery of the troglobious palpigrade Eukoenenia draco (Peyerimhoff 1906) (Palpigradi: Eukoeneniidae), with notes on the adaptations to a cave-dwelling life - Mayoral, J. G.; Barranco, P. (Zootaxa, 2013)
Several females, a male, and an immature of the species Eukoenenia draco (Peyerimhoff, 1906) have been captured recently in Majorca, more than a century after its description. The male of this enigmatic species is described for the first time and the female is redescribed, with new data and figures. The level of adaptation of this species to a cave-dwelling life is discussed and compared with those of other troglobitic species of palpigrades. Comparison of E. draco draco with E. draco zariquieyi (Condé, 1951) reveals substantial differences that lead us to consider E. zariquieyi stat. nov. as a full species.